2020
DOI: 10.1074/jbc.ac120.013056
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral compound remdesivir potently inhibits RNA-dependent RNA polymerase from Middle East respiratory syndrome coronavirus

Abstract: Antiviral drugs for managing infections with human coronaviruses are not yet approved, posing a serious challenge to current global efforts aimed at containing the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Remdesivir (RDV) is an investigational compound with a broad spectrum of antiviral activities against RNA viruses, including SARS-CoV and Middle East respiratory syndrome (MERS-CoV). RDV is a nucleotide analog inhibitor of RNA-dependent RNA polymerases (RdRps).Here, we co-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
773
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(819 citation statements)
references
References 26 publications
(43 reference statements)
7
773
0
17
Order By: Relevance
“…In a rhesus macaque model of MERS-CoV infection, prophylactic remdesivir treatment was initiated 24 h prior to inoculation, and MERS-CoV did not induce clinical disease and did not replicate in respiratory tissues, thus preventing the formation of lung lesions [51] . In cell-based assays, the triphosphate form of remdesivir incorporated at position i, and RNA chain termination was delayed, which explained the high potency of remdesivir against RNA [52] . Remdesivir was used to treat the first case of COVID-19 infection in the United States: the patient's clinical condition improved after only one day of remdesivir treatment [53] .…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…In a rhesus macaque model of MERS-CoV infection, prophylactic remdesivir treatment was initiated 24 h prior to inoculation, and MERS-CoV did not induce clinical disease and did not replicate in respiratory tissues, thus preventing the formation of lung lesions [51] . In cell-based assays, the triphosphate form of remdesivir incorporated at position i, and RNA chain termination was delayed, which explained the high potency of remdesivir against RNA [52] . Remdesivir was used to treat the first case of COVID-19 infection in the United States: the patient's clinical condition improved after only one day of remdesivir treatment [53] .…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…4,46 Remdesivir has demonstrated activity against MERS-CoV and SARS-Cov in vitro and animal models. 82,83 An in vitro study found that remdesivir and chloroquine inhibit viral infection, but further study is required. 84,85 Results from a single study of over 100 COVID-19 patients found chloroquine was superior to control in reducing pneumonia exacerbation, improving imaging findings and virus-negative conversion, and shortening the course of the disease.…”
Section: Treatmentmentioning
confidence: 99%
“…In the light of the One Health concept, control of this emerging virus requires the reduction of the viral shedding to the environment from the main reservoirs, for animal-person transmission and from humans for person-person transmission [35]. Based on the previous experience from the other emerging diseases, particularly SARS-CoV and influenza viruses, avoiding the mixing of various species of animals, birds, and mammals, is highly suggested [51,65,66]. This strategy will minimize the possibility of recombination among not only these pathogens but also for other common pathogens in the near future.…”
Section: Strategies Based On Animal-human Interactionmentioning
confidence: 99%
“…The regular monitoring of various coronaviruses, especially in various species of bats, animals, and birds on the genomic level, is highly recommended. Some studies suggested the most human coronaviruses; including SARS-CoV, MERS-CoV, HCoV-229E, and HCoV-NL63 originated from bats [25,65]. This highlights the mandate for continuous monitoring of the coronaviruses population in bats as an alarm to the emergence of new novel coronaviruses in the future.…”
Section: Strategies Based On the Development Of Novel Vaccines And Anmentioning
confidence: 99%
See 1 more Smart Citation